COUNSELLING AS A REMEDY FOR CORRUPTION IN THE NIGERIAN CIVIL SERVICE - Adamu, Hadiza (Sokoto Educational Review, 2020)
Corruption has taken roots in the Nigerian society as a result of moral decadence. Public officials in Nigeria have deviated from accepted norms to satisfy their private needs. This paper defines what corruption is, its causes and effects and how counselling can be used as an effective tool in eradicating corruption in the Nigerian civil service. It is recommended that a national office for nationhood counselling should be established. A committee of counselors and other experts in the behavioural fields should also be established. This overall and all-embracing philosophy and ideology for the nation is aimed at inculcating into the people our good culture of moral values and the idea of nationalism and patriotism.